The Existence of Private Madrasas in the Era of Capitalization of Education (A Case Study in MTs Muhammadiyah Karangkajen Yogyakarta) - Hopid, Abdul; Wantini, Wantini; Rahman, Arif; Hidayat, Kun; Jhati, Gilang (TARBAWY: Indonesian Journal of Islamic Education, 2023)
The existence of private madrasas in the era of capitalization of education with the input of students from marginal and abangan communities with lower economic conditions is indeed a challenge for madrasa managers. This research was conducted at MTs Muhammadiyah Karangkajen (MTs MK) and aimed at uncovering the factors that become the strengths of madrasas so that madrasas continue to exist and continue to develop even with marginal and abangan backgrounds. The research method uses a qualitative descriptive approach—data collection using in-depth interviews, observation, and documentation. The study results show that the strength factors of MTs MK in the era of educational capitalization are spiritual capital, cultural capital, and social capital, which have implications for economic capital.